In vivo induction of regulatory T cells by anti‐CD45RB antibody causes transferable tolerance to discordant human xenogenic islets. (20th September 2022) - Zhang, Yanling; Yang, Maozhu; Jia, Guiqing; Deng, Shaoping; Lei, Ji; Markmann, James; Zhao, Gaoping
Abstract: Background: The treatment of diabetes by islet cell transplantation has become an accepted therapy, with transplantation of xenogeneic islet cells an attractive alternative to the problem. Previous studies in mice have demonstrated that anti‐CD45RB induce immune tolerance in human pancreatic islet cells. The current study was to define the mechanism of action of anti‐CD45RB induced nonspecific immune tolerance to heteroantigens. Methods: A total of 1500 IEQ human islets were transplanted to diabetic B6μMT‐/‐ mice, B6 mice, and μMT‐/‐ diabetic mice undergoing thymectomy. These mice were treated short‐term with doses of anti‐CD45RB. CD4+Foxp3+Tregs were detected in the blood, peripheral lymphatic organs by flow cytometry, and immunohistochemistry. In addition, anti‐CD25 mAb was administered to tolerant human islet cells B6μMT‐/‐mice. Mice then were transplanted with other human islet cells and received CD4+CD25+Tregs isolated from tolerant human islets mice to observe islet destruction. Results: Anti‐CD45RB treatment‐induced tolerance to islets in both immunocompetent and B‐cell‐deficient mice (μMT‐/‐ mice) by processes that were dependent on CD25+ Tregs, but not B cells. Anti‐CD45RB treatment increased the number of CD4+Foxp3+Tregs cells. Anti‐CD45RB treatment‐induced immune tolerance that was antigen nonspecific, with Tregs playing an important role. Anti‐CD45RB treatment‐induced tolerance generated Tregs that could be transferred to another individual to manifest nonspecific immune tolerance. Conclusion: The results of the experiment suggest that anti‐CD45RB induced tolerance to human islet xenografts is mediated by the proliferation of Tregs. These tolerogenic Tregs can be transferred to other mice and induce nonspecific immune tolerance.